The Welfare Effects of Health-Based Food Tax Policy - Tommi Härkänen; Kaisa Kotakorpi; Pirjo Pietinen; Jukka Pirttilä; Heli Reinivuo; Ilpo Suoniemi (Aboa Centre for Economics (ACE), 2012)
This paper examines the effects of health-oriented food tax reforms on the distribution of tax payments, food demand and health outcomes. Unlike earlier work, we also take into account the uncertainty related to both demand estimation and health estimates and report the confidence intervals for the overall health effects instead of only point estimates. Taxation of sugar leads to a statistically significant reduction in both the incidence of type 2 diabetes and coronary heart disease. The health effects appear to be most pronounced for low-income individuals, and the reforms may therefore reduce health inequality. This effect undermines the traditional regressivity argument against the heavy taxation of unhealthy food.
Keywords: H20; I14; I18; 330; Sin taxes; food taxation; tax incidence; commodity demand; obesity; diabetes; coronary heart disease; bootstrapping